La ambición del orden en juego. Los movimientos sociales, ensayo sobre método y objeto - Jesús Galindo (Estudios sobre las Culturas Contemporáneas)
A methodological proposal on the basis of ethnography, typological construction and social movements conceived as an excellent object of social and historical analysis.